2016
DOI: 10.3389/fmicb.2016.00594
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of Schistosoma mansoni PZQ-Resistant and -Susceptible Strains Are Different in Presence of Praziquantel

Abstract: Schistosomiasis is one of the most common human parasitic diseases whose socioeconomic impact is only surpassed by malaria. Praziquantel (PZQ) is the only drug commercially available for the treatment of all schistosome species causing disease in humans. However, there has been stronger evidences of PZQ-resistance on Schistosoma mansoni and thus it is very important to study the phenotypic characteristics associated with it. The aim of this study was to evaluate morphological alterations in S. mansoni PZQ-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 57 publications
2
37
0
1
Order By: Relevance
“…In addition to tegumental damage, PZQ significantly changed the metabolic profile of both sexes of S. mansoni [49]. These data are supported by a recent work where tegumental damage of schistosomes under PZQ exposure was demonstrated through scanning electronic microscopy and optical microscopy [92]. These findings could be helpful for understanding possible targets and pathways of this antischistosomal drug and demonstrates the versatility and potential use of mass spectrometrybased metabolomics for identification of drug targets.…”
Section: Searching For Drug Targets At Helminthiasis-praziquantel Andsupporting
confidence: 76%
“…In addition to tegumental damage, PZQ significantly changed the metabolic profile of both sexes of S. mansoni [49]. These data are supported by a recent work where tegumental damage of schistosomes under PZQ exposure was demonstrated through scanning electronic microscopy and optical microscopy [92]. These findings could be helpful for understanding possible targets and pathways of this antischistosomal drug and demonstrates the versatility and potential use of mass spectrometrybased metabolomics for identification of drug targets.…”
Section: Searching For Drug Targets At Helminthiasis-praziquantel Andsupporting
confidence: 76%
“…In regard to collagen alpha chain, Yang and colleagues (Yang et al, 2012)described that silencing the expression of a type of collagen (type V collagen) significantly affects the spawning and egg hatching of S. japonicum , and it also affects the morphology of the worms (Yang et al, 2012). Therefore, it would be very interesting evaluate the role of each of these proteins in PZQ-resistance, specially, collagen alpha chain, since it seems to occur morphological alterations in eggs and worms of S. mansoni PZQ-resistant strain (Pinto-Almeida et al, 2016). Moreover, females of this species, the only gender in which those proteins were found in this work, are more tolerant to PZQ treatment than males (Pinto-Almeida et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…All those results together represent an important finding for the study of PZQ-resistance/susceptibility in S. mansoni , since they allow comparing directly the proteome under both conditions. We believe that the most promising candidates are proteins that appeared associated only to one of the strains, especially those with functions possibly related with the phenotypic alterations observed in (Pinto-Almeida et al, 2016), or previously associated with resistance by others parasites to different drugs. These candidates require special attention in more studies, assessing for instance the level of protection induced by these proteins in animal models infected by both S. mansoni strains, as they may have some involvement on PZQ-resistance phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, juvenile parasites, between 7 and 28 days old, appear to be less susceptible to this drug . In addition, studies have shown the emergence of Schistosoma strains that are less sensitive to PZQ …”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, studies have shown the emergence of Schistosoma strains that are less sensitive to PZQ. [14][15][16][17][18][19] Considering the importance of natural products in drug discovery processes, 20 a wide variety of extracts and compounds isolated from plants have been chemically and biologically investigated against Schistosoma parasites and their invertebrate host, 21,22 as well as other snails. 23 Curcuma longa L. Zingibiraceae, also known as turmeric, is widely used in culinary and folk medicine to treat several diseases.…”
Section: Introductionmentioning
confidence: 99%